2014
DOI: 10.1016/j.nima.2013.08.077
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI insert using digital SiPMs: Investigation of MR-compatibility

Abstract: In this work, we present an initial MR-compatibility study performed with the world's first preclinical PET/MR insert based on fully digital silicon photo multipliers (dSiPM). The PET insert allows simultaneous data acquisition of both imaging modalities and thus enables the true potential of hybrid PET/MRI. Since the PET insert has the potential to interfere with all of the MRI's subsystems (strong magnet, gradients system, radio frequency (RF) system) and vice versa, interference studies on both imaging syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 13 publications
1
70
0
Order By: Relevance
“…Some authors have reported on the performance parameters of SiPM-based full-ring preclinical PET systems or MRI inserts (4,10,18,19). However, only some of the NEMA NU 4 measurement protocols have been performed on these systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported on the performance parameters of SiPM-based full-ring preclinical PET systems or MRI inserts (4,10,18,19). However, only some of the NEMA NU 4 measurement protocols have been performed on these systems.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that we did not take into account the performance of the systems in high magnetic fields. However, other research groups have already proved the stability and proper performance of SiPMs in MRI systems (18,19). Although both MiniPET systems have a relatively small field of view compared with other preclinical PET systems (16,21,25), the main goal of this study was to compare SiPM with PMT technology while keeping scintillation crystal geometry, system matrix, slice rebinning algorithm, and even image reconstruction identical.…”
Section: Discussionmentioning
confidence: 99%
“…Wehner et al (19) based on SiPM technology with fully front-end digitizers. The signals from PET detectors are directly digitized and processed within the magnetic field.…”
Section: Petmentioning
confidence: 99%
“…For example, digital optical communication over fiber was used to avoid electrical data connections in an MRI-compatible preclinical PET scanner. 11,12 While this technique has the advantage of avoiding the mutual interference that can accompany electrical cables, digitally compresses event data onto a single fiber, and achieves excellent timing resolution, it also requires digital processing electronics housed within the detector modules. These components can draw high power, generate considerable heat, and require more stringent shielding design for operation in an MRI.…”
Section: Introductionmentioning
confidence: 99%